Gradient colour deviation in woven textiles to correspond to pictorial images in diversity. Issue 1 (2nd January 2016) - Kim, Ken Ri; Ng, Frankie; Zhou, Jiu; Hu, Jinlian
ABSTRACT: This study aims to propose optimal weaving conditions for creation of a natural shading effect in woven textiles. By applying the weave structure and pattern theories, the two core parts of weaving are explored and examined towards improving realisation of gradient weave colours. When planning experiments, weave repeat sizes from 12- to 30-thread are created into a shaded weave series and compounded in a multi-weft figuring method. In terms of weave pattern, a colour spectrum image is designed and its split primary colour layers (e.g. cyan, magenta, yellow and black) are employed as a weave pattern. In conjunction with varied weaving conditions, a colour spectrum image is reproduced in 19 different woven forms. In this study, comparative analysis is approached based on the samples resulted from trials and the practical research is explained in detail of weave structure and weave pattern specifications to propose the core principle of establishing gradient colour deviation.